Antarctic ascidians under increasing sedimentation: Physiological thresholds and ecosystem hysteresis - Torre, Luciana (2021)
Glacier melting sediment inputs affect coastal ecosystems on the Antarctic Peninsula. In Potter Cove (South Shetland Islands, Antarctica), the shift from an “ascidian dominated” to a “mixed” assemblage has been linked to sedimentation. However, in recently described newly ice-free areas ascidians became dominant in spite of total suspended particulate matter (TSPM) concentrations, which are the highest measured in Potter Cove. Here, we compared the gut content and energy reserve of three ascidian species at three stations under different TSPM regimes. All analysed species had a higher gut content with lower %OM at these newly areas. A theoretical relationship between the scope for growth for the targeted ascidians and TSPM explained assemblages’ recorded change but failed to explain current ascidians distribution. The results may indicate the existence of a TSPM threshold that allows the spatial coexistence of alternative stable states at benthic Potter Cove system.